PENGARUH MOTIVASI, IKLIM ORGANISASI DAN PENGEMBANGAN KARIR TERHADAP KOMITMEN ORGANISASIONAL DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA CV.MAYA ANTIQUE - Putra, Rafinarezka Hendi; Supriyono, Supriyono; Subono, Agung (Universitas Muria Kudus, 2024)
This study aims to determine and analyze the influence of motivation, organizational climate, career development on organizational commitment and job satisfaction as an intervening variable on CV. Maya Antique. The research method used is a quantitative method using primary data. For data collection, 112 employees were processed using SEM-Amos. The results of the research analysis show that work motivation has a positive and significant effect on job satisfaction (1) Organizational climate has a positive and significant effect on job satisfaction (2) Career development has a positive and significant effect on job satisfaction (3) Work motivation has a positive and significant effect on organizational commitment (4) Organizational climate has no significant effect on organizational commitment (5) Career development has no significant effect on organizational commitment (6) Job satisfaction has a positive and significant effect on organizational commitment (7).